"This Feminism is Transformative, Rebellious and Autonomous": inside struggles to shape the CFS Voluntary Guidelines on Gender Equality and Women's Empowerment. Issue 7 (9th August 2022) - MacInnis, Jessie; Wiebe, Nettie; Desmarais, Annette Aurélie; Montenegro de Wit, Maywa
ABSTRACT: The Women's Working Group of the Civil Society and Indigenous Peoples' Mechanism (CSM) of the Committee on World Food Security (CFS) has long advocated for policies reflective of gender equity in agriculture and food systems rooted in agroecology, human rights, and food sovereignty. In 2021, after years of activism, a series of drafts toward a set of Voluntary Guidelines on Gender Equality and Women's Empowerment were produced by the CFS. With contributions from members of the CSM and La Via Campesina, we provide insights into the struggles, critiques, and paths forward for continued engagement with the CFS on this heavily politicized topic.